2006
DOI: 10.1080/03079450500465791
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine pancreatic insufficiency in pigeons

Abstract: Exocrine pancreatic insufficiency (EPI) is a well-studied syndrome in domestic animals. EPI occurs when severe progressive loss of tubulo-acinar tissue from atrophy or inflammatory destruction results in insufficient secretion of digestive enzymes and clinical signs of malabsorption. However, the literature on EPI in birds is limited. The syndrome has been previously described in several cases where the diagnosis was based on clinical signs due to malabsorption-like light-coloured voluminous faeces, voracious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Reference plasma lipase levels for chickens are not yet available. In pigeons, reference physiological values indicate plasma lipase activity between 0 and 5 U/L (Amann et al, 2006). These values were greatly exceeded in the infected groups in this study.…”
Section: Inclusion Bodies Necrosiscontrasting
confidence: 57%
“…Reference plasma lipase levels for chickens are not yet available. In pigeons, reference physiological values indicate plasma lipase activity between 0 and 5 U/L (Amann et al, 2006). These values were greatly exceeded in the infected groups in this study.…”
Section: Inclusion Bodies Necrosiscontrasting
confidence: 57%
“…Histological studies of pancreatic lesions in broilers with RSS revealed fibrosis, inflammation, vacuolar changes in the exocrine compartment, degeneration of acinar cells and loss of zymogen granules (Qamar et al 2013). In pigeons, exocrine pancreas disease produced voluminous, coloured faeces and weight loss (Amann et al 2006), and when aflatoxins are present in the diet, histological changes in the pancreas are observed, together with effects on performance and nutrient absorption (Marchioro et al 2013). Together, these findings establish a relationship between pancreatic damage and signs of malabsorption, and, more importantly, a relationship between pancreatic damage and RSS.…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between the activities of pancreatic enzymes in the pancreas and blood serum were studied in pet animals (e.g. dogs) as related to the acute and/or chronic pancreatitis; exocrine pancreatic insufficiencies in poultry are considered less significant and hence these interrelationships in avian species are still understudied [8]. There is a lack of available information on the interrelationships between the tryptic activities in pancreatic juice and blood serum in poultry [3].…”
mentioning
confidence: 99%